Contesting paternity by the biological father in German and Belarusian law: different solutions for the same issue - Wudarski, Arkadiusz; Tsarova, Liudmila V. (Journal of the Belarusian State University. Law, 2024)
The paper examines issues related to the right of a biological but non-legal father to contest legal fatherhood. The analysis is based on German law and involves considerations regarding the mutual relations among various forms of fatherhood and the relation of each to children and other family members. Attention is paid to differences in requirements that have to be met in order to contest fatherhood between biological and legal fathers, in time limits for contestation and in the legal consequences of contestation. The meaning of the term «social and family relationship», the role of social fatherhood, the constitutionality of the German regulations and their conformity with the European Convention for the Protection of Human Rights and Fundamental Freedoms are also discussed. The comparative analysis with Belarusian family law demonstrates substantial differences in the regulation of contesting fatherhood by biological father from the German approach. At the same time, the issue of finding a balance between conﬂicting legally protected interests, in particular the right to family protection, fathers’ rights, the best interest of the child and the right to know one’s own identity remains relevant for the legislation of both countries.